2019
DOI: 10.1016/j.nicl.2019.102038
|View full text |Cite
|
Sign up to set email alerts
|

fMRI functional connectivity as an indicator of interictal epileptic discharges

Abstract: Functional connectivity to successful EEG/fMRI response indicates higher IED rates.The results hold when correcting for distance to maximum EEG-fMRI and laterality.Intracranial IED rates correlate with functional connectivity to EEG/fMRI maxima.Results suggest it is feasible to non-invasively infer the brain regions with IEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Su et al ( 130 ) identified the different types of IEDs according to the spatial distributions from 38 patients with focal epilepsy and were used separately in the analysis of IED-related BOLD responses. The concordance between the maximal BOLD responses and the SOZ was found using iEEG, and then the functionally connected zone was determined for each one using the maximal BOLD as a seed ( Figure 10 ).…”
Section: Localization Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…Su et al ( 130 ) identified the different types of IEDs according to the spatial distributions from 38 patients with focal epilepsy and were used separately in the analysis of IED-related BOLD responses. The concordance between the maximal BOLD responses and the SOZ was found using iEEG, and then the functionally connected zone was determined for each one using the maximal BOLD as a seed ( Figure 10 ).…”
Section: Localization Approachesmentioning
confidence: 99%
“…(D) The number of IEDs in each channel was normalized by the median number of IEDs in each subject. Statistical analysis was performed to determine group difference of IED rates between channels inside and outside the FCZ ( 130 ).…”
Section: Localization Approachesmentioning
confidence: 99%
See 3 more Smart Citations